IMPACT OF INTERNET ADDICTION ON A YOUNG ADOLESCENT BOY: AN INTERVENTIONAL CASE REPORT - Dubey, Jyoti; Saxena, Rashmi (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Nowadays, the use of the internet and technology has become a boon. However, like a two-sided coin, it has both positive and negative impacts on our lives. As part of the positive changes in our lives, technology enables us to connect with people around the world and send messages to different parts of the country within a fraction of a second. However, excessive use of the internet can lead to addictive behavior like cyber bullying, online shopping, and taking away time from studies and other important activities such as physical activities. Therefore, in this case report, we aim to teach our client therapeutic techniques to promote the healthy use of the internet and prevent compulsive internet usage.